Roadside Erosion in Himachal Pradesh - Shabnam, S R (Journal of Soil and Water Conservation, 2022)
The Centrally administered territory of Himachal Pradesh, with an area of 11,000 square miles, is spread over altitudes ranging from about 1,100 to 20,000 ft. above sea level. Over 75 per cent of the total area lies between altitudes 3,000 and 20,000 ft. the exception of the low altitude, fertile Bahal vallev in the Mandi district and the Paonta valley in the Sirmur district, which are the granaries of the Pradesh, there are no vast, easily accessible valleys. Its sparse population of 1,100,000 souls lives in 14,000 villages scattered over deep, narrow valleys, difficult, steep slopes and mountain tops, and is essentially an agricultural one, forestry and cattle rearing being their subsidiary sources of income. The total cattle wealth is about 2,500,000 heads, out of which 1,200,000 are sheep and goats. The incidence of grazing over the area available for grazing is very high, and goat — enemy No. 1 of vegetation — presents a serious threat. The annual rainfall varies from about 30 in. at low altitudes to 70 in. at high alti- tudes, the bulk of which is delivered from June to August. Above 6,000 ft., snow re- gularly falls from October to April, when all kinds of traffic on roads and paths are either paralysed or brought to a standstill,